2018
DOI: 10.2147/copd.s162713
|View full text |Cite
|
Sign up to set email alerts
|

Coronary lesions in patients with COPD (Global Initiative for Obstructive Lung Disease stages I–III) and suspected or confirmed coronary arterial disease

Abstract: BackgroundSystemic inflammation is the pathophysiological link between coronary artery disease (CAD) and COPD. However, the influence of subclinical COPD on patients with suspected or diagnosed CAD is largely unknown. Thus, this study was designed to evaluate the degree of coronary involvement in patients with COPD and suspected or confirmed CAD.MethodsIn this cross-sectional study, carried out between March 2015 and June 2017, 210 outpatients with suspected or confirmed CAD were examined by both spirometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Patients in the COPD group were older and had a higher frequency of diabetes compared with those in the non-COPD group; however, COPD remained an independent predictor of long-term cardiovascular events even after adjusting for established risk factors for CAD such as age, gender, hypertension, diabetes, and dyslipidemia. Patients with COPD also had a higher frequency of CAD, mainly severe and multivessel, and the more advanced the degree of COPD, the greater the severity of the coronary lesions and the extent of calcification, as previously suggested by us 29 and others. 30 Epidemiologic studies have identified a strong association between COPD and CAD, leading to the proposition that patients with COPD might be at higher risk of developing CAD and vice versa.…”
Section: Discussionsupporting
confidence: 81%
“…Patients in the COPD group were older and had a higher frequency of diabetes compared with those in the non-COPD group; however, COPD remained an independent predictor of long-term cardiovascular events even after adjusting for established risk factors for CAD such as age, gender, hypertension, diabetes, and dyslipidemia. Patients with COPD also had a higher frequency of CAD, mainly severe and multivessel, and the more advanced the degree of COPD, the greater the severity of the coronary lesions and the extent of calcification, as previously suggested by us 29 and others. 30 Epidemiologic studies have identified a strong association between COPD and CAD, leading to the proposition that patients with COPD might be at higher risk of developing CAD and vice versa.…”
Section: Discussionsupporting
confidence: 81%
“…There are evident epidemiologic data connecting COPD with CAD. In a cross-sectional study of patients with suspected CAD, patients with COPD had a significantly higher frequency of obstructive coronary lesions as compared with CAD patients without airflow limitation [31]. Additionally, the severity of airflow limitation correlated with coronary lesion size and quantity.…”
Section: Coronary Artery Disease In Copdmentioning
confidence: 99%
“…Spirometry tests, especially FEV1, and airflow obstruction defined as FEV1/FVC less than 0.70, for instance, have strong predictive potential for CAD. For every 10% decrease in FEV1, cardiovascular mortality was found to increase by about 28%, and even among individuals with severe airways obstruction, the leading causes of death are predominantly sequels of cardiovascular disease [31,32,33,34]. On the other side, studies investigating airflow limitation in patients with CAD are scarce, but the prevalence of obstructive ventilation in CAD patients might be underestimated in the literature [28].…”
Section: Coronary Artery Disease In Copdmentioning
confidence: 99%
“…In another study from Brazil, the prevalence of CHD was 88% among 101 COPD patients compared with 45% among 109 non-COPD controls [ 28 ]. In this study smoking habits varied greatly between study groups, and the prevalence of CHD in both groups were quite high.…”
Section: Discussionmentioning
confidence: 99%